Rise in cesarean section rate over a 20-year period in a public sector hospital in northern Thailand - Charoenboon C. (2014)
Objective: To determine a trend of cesarean section rate (CSR) and main contributing factors in a public sector hospital, representing northern part of Thailand. Methods: A retrospective descriptive analysis was conducted by assessing the database of maternal-fetal medicine unit, which had prospectively been collected for 20 years. Trends were evaluated using data for the years 1992-2011. Private sector patients were excluded. Results: A total of 50,872 public sector patients were available for analysis. The number of deliveries was gradually decreased from 3,802 in 1992 to 1,748 in 2011. Of them, 7,480 underwent cesarean section, CSR of 14.7 %. However, the CSR was significantly increased from 11.3 % in 1992 to 23.6 % in 2011 (p value <0.001). The CSRs indicated by cephalopelvic disproportion (CPD) and previous CSs were mainly responsible for a marked increase over the study period. CSR due to CPD was increased from 3.2 % in 1992 to 7.9 % in 2011 (p value <0.0001). While CSR due to other indications either breech presentation, fetal distress and twin pregnancies were only slightly, but significantly increased in the last decades but they are relatively constant in the recent years. Conclusions: In our public sector, CSR has gradually increased. The main reasons of such an increase were likely to be associated with over-diagnosis of CPD and subsequent repeated CS, while other indications played only a minimal role. To achieve the appropriate CSR, audit system for diagnosis of CPD must be instituted. © 2012 The Author(s).